Juridical Analysis of Patient Data Protection in National Legal Perspective - Frahma, Elen Anedya (UNTAG Law Review, 2024)
The emergence of digital-based health services has garnered increased attention following the onset of the COVID-19 pandemic. The utilization of these services involves the collection of user data, a sensitive matter that holds the potential for giving rise to legal issues, thereby calling for the need for regulations concerning the protection of personal data. Indonesia has established provisions to safeguard personal data in the health sector through various legal instruments. However, the effective protection of users' data in the digital transformation of the health sector has not materialized. This is evident in instances of personal data breaches involving participants of the Health Social Security Administering Agency. The research is conducted using normative juridical legal research methods. The findings highlight the context of personal data protection in the health sector within the digital era, which is regulated in, for example, article 26 of the ITE Law, Law Number 43 of 2009 regarding Archives, article 57 of the Health Law, Minister of Health Regulation Number 24 of 2022 concerning Medical Records and Law Number 36 of 1999 on Telecommunications. Nevertheless, the occurrence of data leaks from BPJS Health indicates the failure to ensure personal data protection in the health sector in Indonesia. As a result, regulations and stringent supervision within health institutions, particularly in the digital sector, are crucial. The appointment of Data Protection Officers in health service agencies represents the solution to these issues, and it is imperative to realize digital protection of personal data in the health sector.